The Influence of Chief Executive Officer Characteristics on Biodiversity Disclosure - Khasanah, Putri Azizah Nur; Wijayanti, Rita (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study aims to analyze how biodiversity disclosure can be influenced by CEO characteristics, which are proxied by CEO age, education level, environmental knowledge, and international experience. Methodology: This research uses secondary data obtained from sustainability reports and annual reports of non-financial companies listed on the Indonesia Stock Exchange during the period 2020–2022. The sample consists of 232 companies selected using the purposive sampling method. The methodology used in this study is multiple regression analysis, which is quantitative. Results: The results of the study show that CEO age, company size, profitability, and environmental certification have a positive impact on biodiversity disclosure. However, CEO education level, environmental knowledge, international experience, and leverage do not affect biodiversity disclosure. Applications/Originality/Value: This study finds that the role of the CEO is significant in initiating biodiversity disclosure activities in companies. CEO decisions play an important role in adopting better biodiversity disclosure practices. Therefore, companies may consider appointing more mature CEOs to support the improvement of environmental disclosure.